Sexual Symmetry : Love in the Ancient Novel and Related Genres. - Konstan, David (Princeton legacy library., 2014)
""In the Greek romances, "" writes David Konstan, ""sighs, tears, and suicide attempts are as characteristic of the male as of the female in distress; ruses, disguises, and outright violence in defense of one's chastity are as much the part of the female as of the male."" Exploring how erotic love is represented in ancient amatory literature, Konstan points to the symmetry in the passion of the hero and heroine as a unique feature of the Greek novel: they fall mutually in love, they are of approximately the same age and social class, and their reciprocal attachment ends in marriage. He shows.